Reassessing Labour Market Reforms: A Critique - Pramod N. (Raja) Junankar; Muhunthan Jayanthakumaran (Institute for the Study of Labor (IZA), 2014)
This paper provides a critique of Faccini (2014) that allegedly shows that temporary contracts lead to lower unemployment in Europe. Using Faccini's data and his estimation methods, we show that the Fixed Effects estimation results collapse when we make slight alterations in the sample size or the independent variables used. The Arellano-Bond estimates are meaningless since the number of instruments is almost equal to the number of observations. To conclude we find that there is no evidence to support the conclusion that greater use of temporary contracts would decrease unemployment.
Keywords: J64; J01; J08; J21; 330; unemployment; temporary contracts; employment protection